3,4-Dimethyl-N-(2,4,5-trimethoxybenzylidene)-1,2-isoxazol-5-amine - Tan, Kong Wai; Ng, S.W.; Asiri, A.M.; Khan, S.A. (International Union of Crystallography, 2010)
In the title compound, C(15)H(18)N(2)O(4), the aromatic rings on the azomethine double bond are trans to each other [C-C=N-C torsion angle = -178.29 (12)degrees] and they are approximately coplanar, the dihedral angle between them being 5.0 (1)degrees.